The research on the effect of digital economy development on urban air quality - Song, Baolin; Shi, Haozhe; Wang, Mengxin; Gu, Ran (Frontiers in Environmental Science, 2022)
Digital economy and air quality are the key issues concerned by the government and academia. The healthy and sustainable development of the digital economy and the continuous optimization of urban air quality are not only conducive to high-quality economic development but also closely related to people’s livelihood. Based on the panel data of 228 cities from 2015 to 2020, using the panel regression and the mediating effect test methods, this paper verifies the impact of the digital economy development on urban air quality and then further analyzes the heterogeneity. The main results are as follows. Digital economy development can effectively improve urban air quality. The mediating effect of the urban industrial structure advancement accounts for 17.27%, and that of urban TFP accounts for 14.55%. The effect of improving air quality in cities with a high-level digital economy is more prominent, and the effect in large and medium-sized cities is more extensive. Meanwhile, in cities with a high urbanization rate, the effect of digital economy on improving air quality is more prominent.